2013
DOI: 10.1111/eci.12147
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease: a risk factor for type 2 diabetes: a nationwide population‐based study

Abstract: Patients with COPD have a higher risk of type 2 diabetes compared with control subjects after adjusting for confounding factors such as sex, age, residential area, insurance premium, steroid use, hypertriglycemia, hypertension, CAD and cerebrovascular disease. Continuous surveillance of signals of dysglycemia may be incorporated into care programmes for patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 18 publications
(35 reference statements)
1
39
1
7
Order By: Relevance
“…Lee et al conducted a large 5.5-year follow-up study and found that COPD patients had a significantly higher rate of incident type 2 diabetes compared with that of healthy individuals, HR ¼ 1.41 after adjusting for sex, age, residential area, insurance premium, steroid usage and cardiovascular diseases [17]. However, they had no information on smoking status or BMI, which, in our study, were significant confounders.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Lee et al conducted a large 5.5-year follow-up study and found that COPD patients had a significantly higher rate of incident type 2 diabetes compared with that of healthy individuals, HR ¼ 1.41 after adjusting for sex, age, residential area, insurance premium, steroid usage and cardiovascular diseases [17]. However, they had no information on smoking status or BMI, which, in our study, were significant confounders.…”
Section: Discussioncontrasting
confidence: 52%
“…In particular, an increased risk of type 2 diabetes in patients with COPD was found in some studies [16,17], whereas other studies did not find any association between COPD and type 2 diabetes, or between metabolic syndrome and obstructive airway limitation [18e21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when considering baseline lung function, according to the modified Global Initiative for Obstructive Lung Disease (GOLD) criteria, subjects with GOLD stage 3 or 4 COPD had a higher prevalence of diabetes [2], a result later confirmed by another study [52]. Thus, COPD appears to constitute an important risk factor for developing T2DM, and several studies have identified that the prevalence of diabetes is higher in COPD patients [15,16,53,54,55]. Over a follow-up period of 20.9 years, the Normative Aging Study found that FVC, FEV 1 and maximal midexpiratory flow rate (MMEF) were associated with insulin resistance [56].…”
Section: The Impact Of Copd On Patients With Diabetesmentioning
confidence: 99%
“…diabetics with neuropathy) [14]. Conversely, it has also been suggested that COPD constitutes an important risk factor for the development and/or progression of T2DM [2,15,16,17], a phenomenon that does not apply to type-1 diabetes. Thus, although COPD and T2DM represent distinct disease entities, there might indeed be a pathophysiological connection that links these important chronic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, COPD is known to be associated with several important chronic comorbid diseases [2]. In particular, recent evidence has supported that COPD may constitute an important risk factor for the development of type-2 diabetes [2,3], and several studies have identified an increased prevalence of diabetes in COPD patients [4,5,6,7,8]. …”
Section: Introductionmentioning
confidence: 99%